Conventional control in the trials of necessary divorce from the state of Tabasco (Revista de Investigaciones Universidad del Quindío, 2021)
In this article the problem of the 272 Civil Code law from Tabasco is analyzed. It states certain hypotheses or causes, which have to be accredited or justified to proceed with the necessary divorce in the state. Due to the part that our country takes in international treaties, it is pointed out that every person has the right of freedom, as well as the acknowledgement of his/her legal personality. Hence the obligation of the legal authorities of performing the conventional control. It also mentions that local judges are not fully capable of determining the unconstitutionality of a norm therefore making a general statement about the human rights established in the constitution and the international treaties. As it happens in the direct control line, widely expressed in the laws 103, 107, and 105 in the constitution. On these grounds the importance of the conventional control relies on the trials of necessary divorce.
Keywords: Conventional Control; needed divorce procedure